Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3791/54067
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous DNA-RNA Extraction from Coastal Sediments and Quantification of 16S rRNA Genes and Transcripts by Real-time PCR

Abstract: Real Time Polymerase Chain Reaction also known as quantitative PCR (q-PCR) is a widely used tool in microbial ecology to quantify gene abundances of taxonomic and functional groups in environmental samples. Used in combination with a reverse transcriptase reaction (RT-q-PCR), it can also be employed to quantify gene transcripts. q-PCR makes use of highly sensitive fluorescent detection chemistries that allow quantification of PCR amplicons during the exponential phase of the reaction. Therefore, the biases ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…The primers used for quantification of bacterial 16S rRNA were 341f -CCTACGGGNGGCWGCAG and 785r -GACTACHVGGGTATCTAATCC (Klindworth et al, 2013). qPCR reactions were performed using a CFX384 TM Real-Time PCR Detection System (BioRad) using reagents, cycle conditions, and standards as previously described (McKew and Smith, 2015;Tatti et al, 2016). Inspection of standard curves showed that all assays produced satisfactory efficiency (74%) and R 2 values (>0.99).…”
Section: Polycyclic Aromatic Hydrocarbon Analysismentioning
confidence: 99%
“…The primers used for quantification of bacterial 16S rRNA were 341f -CCTACGGGNGGCWGCAG and 785r -GACTACHVGGGTATCTAATCC (Klindworth et al, 2013). qPCR reactions were performed using a CFX384 TM Real-Time PCR Detection System (BioRad) using reagents, cycle conditions, and standards as previously described (McKew and Smith, 2015;Tatti et al, 2016). Inspection of standard curves showed that all assays produced satisfactory efficiency (74%) and R 2 values (>0.99).…”
Section: Polycyclic Aromatic Hydrocarbon Analysismentioning
confidence: 99%
“…Furthermore, inspection of standard curves showed that all assays produced satisfactory efficiency (85%) and R 2 values (>0.99). All qPCR reactions were performed using a CFX384 TM Real-Time PCR Detection System (BioRad) using reagents, cycle conditions, and standards as previously described (McKew and Smith, 2015;Tatti et al, 2016).…”
Section: Hydrocarbon Degradation (Gc-ms)mentioning
confidence: 99%
“…Some of them are marketed as RNA only or DNA only but actually co-extract very efficiently. However, commercially available co-extraction kits often have many steps for that the nucleic acids need to be transferred many times during the process14, and these kits are designed for DNA and RNA extraction from plasma or materials rich in DNA and RNA1214151617. In contrast, few protocols are available for the extraction of integrated DNA and RNA from sputum samples, which contain large amounts of factors such as mucoproteins which wrap up nucleic acids make it hard to be extracted, saccharides, and lipids which make it hard to extract pure nucleic acids from the sputum, especially fragile RNA1819.…”
mentioning
confidence: 99%